Language Learning and Teaching as Social Inter-action
XIV, 300 p.
Keywords: This volume brings together contributions by leading researchers of the social interactional and socio-cultural approaches to language learning and teaching. It provides both an introduction to this important growth point and also an overview of cutting edge research, covering a wide range of language learning and teaching contexts.